Upaya Penurunan Stunting Melalui Pendekatan Multi-Sektoral: Suatu Tinjauan Riteratur - Jihan Defri Wahyuni; Raina Tshalasha; Sonya Putri Anggraini; Boni Saputra; M. Fachri Adnan (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Stunting remains one of the most serious global public health and human development problems, particularly in low- and middle-income countries. The complexity of stunting's causes suggests that it cannot be addressed solely through health sector interventions but requires multisectoral collaboration involving nutrition, sanitation, education, social protection, economic development, and governance. This study aims to analyze multisectoral approaches to stunting reduction across countries through a literature review. The study used 20 academic journals indexed by Scopus and SINTA published between 2020 and 2026. Data were analyzed using a thematic synthesis focusing on governance, collaborative policies, institutional synergies, and integrated intervention models. Findings indicate that countries that successfully reduce stunting generally implement strong collaborative governance, integrated policy implementation, institutional coordination, and nutrition-sensitive interventions. Furthermore, political commitment, local governance, and institutional capacity are identified as important determinants in accelerating stunting reduction. This study contributes to the public administration perspective by emphasizing the importance of multisectoral governance and collaborative public policies in addressing stunting globally.